A shrimp gene encoding a single WAP domain (SWD)-containing protein regulated by JAK-STAT and NF-κB pathways. (March 2020) - Yang, Linwei; Luo, Mengting; Guo, Zhixun; Zuo, Hongliang; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: Regulation of immune responses in animals is largely governed by the JAK-STAT and NF-κB pathways, which are conserved across vertebrates and invertebrates. At present, the relationship between these two pathways in invertebrates remains unclear. In the current study, a novel antimicrobial peptide termed LvSWD5 belonging to the Crustin family was identified from Pacific white shrimp Litopenaeus vannamei . The mature LvSWD5 peptide containing a single WAP domain (SWD) could directly bind bacteria and fungi and inhibit the growth of both Gram-positive and -negative bacteria in vitro . The LvSWD5 promoter was predicted to contain binding sites for STAT and NF-κB and could be regulted by the JAK-STAT and Relish pathways. The expression of LvSWD5 was up-regulated during bacterial, viral and fungal infections and silencing of LvSWD5 in vivo affected the expression of a series of immune related genes and decreased the phagocytic activity of hemocytes against V. Parahaemolyticus . Moreover, the susceptibility of shrimp to V. parahaemolyticus and white spot syndrome virus (WSSV) was significantly increased after silencing of LvSWD5, indicating that LvSWD5 could be involved in antibacterial and antiviral responses. These suggested that the JAK-STAT and NF-κB pathways could converge at the promoter level of a common target gene to regulate the immunity in shrimp. Highlights: Identification of a novel SWD gene (LvSWD5) from Litopenaeus vannamei. Expression of LvSWD5 is regulated by JAK-STAT and Relish pathways. LvSWD5 protein has bacterial binding and bacteriostatic activities. LvSWD5 is involved in immune regulation and immune responses in shrimp.